The Relationship among Parenting Style, Self-Regulation, and Smartphone Addiction Proneness in Indonesian Junior High School Students - Lailil Fatkuriyah; Chae Sun-Mi (Universitas Muhammadiyah Yogyakarta, 2021)
Background: Smartphone addiction leads to physical, psychological, and social consequences for users, particularly for adolescent users, as psychological development is still in the process of maturation. Individual and family characteristics are shown to contribute to shaping adolescent’s behavior related to smartphone usage. Specifically, perceived parenting style and self-regulation have been reported as significant factors influencing smartphone addiction among adolescents.Objective: This study aims to identify the relationship among parenting style, self-regulation, and smartphone addiction proneness in Indonesian junior high school students.Method: This study used a cross-sectional, descriptive study design. Data collection took place in five public junior high schools in Jember from the 7th of January to the 8th of February, 2019. The total sample of this study was 158, purposively asked to fill out three questionnaires: Parental Authority Questionnaire, Self-Regulation Questionnaire, and Smartphone Addiction Proneness Scale. Chi-square test and Pearson’s correlation coefficients were used to test the relationship between two variables.Result: The differences in smartphone addiction proneness between the risk group and non-risk group were significant depending on gender (p=0.004), daily smartphone usage time (p=0.025), and purpose of smartphone usage (p=0.001). A significant negative correlation was found between self-regulation and smartphone addiction proneness (r= -0.448, p=0.001).Conclusion: The current study found that 11.4% of junior high school students in Jember-Indonesia were categorized into risk groups for smartphone addiction. Gender, daily smartphone usage time, and purpose of smartphone usage showed significant differences between the risk group and the non-risk group. However, there was no difference in the parenting style of the mother between the two groups. Self-regulation showed a significant association with smartphone addiction.